Desgaste superficial do esmalte dental após microabrasão in vitro - Zuanon, Angela Cristina Cilense [UNESP]; Azevedo, Elcilaine [UNESP]; Lima, Luciana Monti; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2010)
The aim of this study was to investigate the enamel wear permanent teeth after plastic stick or low speed rubber cup microabrasion. Ten permanent molars were selected to evaluate enamel wear which were sectioned into mesial and distal halves. Each half of the molars was randomly assigned to one of two experimental groups (n = 10) according to the enamel microabrasion technique: plastic stick (GE) or rubber cup (GT). In both the groups, the enamel was submitted to 10 applications of an abrasive paste comprised of 35% phosphoric acid and pumice powder. The paste was applied for 20 seconds under a pressure of 30 g using the instrument defined for each group (plastic stick or rubber cup). The specimens were evaluated under a stereomicroscope connected to a computer. The enamel wear no was statistically different between GE and GT, which presented a mean wear of 304.74 µm (21.20%) and 338.35 µm (22.75%). In conclusion, superficial enamel wear was seen for both the groups, independent of the technique used for the accomplishment of the microabrasion.

O objetivo do presente estudo foi investigar o desgaste superficial após a realização da técnica de microabrasão com o auxílio de espátula plástica ou taça de borracha em baixa rotação. Dez molares permanentes (superfície vestibular) foram utilizados para a avaliação do desgaste superficial, sendo divididos nos grupos: GE (espátula) e GT (taça). Os grupos foram submetidos a dez aplicações de pasta abrasiva composta de ácido fosfórico a 35% mais pedra pomes, com duração de 20 segundos cada, sob pressão de 30 g, utilizando-se a técnica de acordo com cada grupo experimental. Os espécimes foram avaliados em lupa estereoscópica acoplada a um programa de computador. Pôde-se observar para os grupos GE e GT que o desgaste médio foi de 21,20 e 22,75%, respectivamente, não se apresentando diferença estatística entre eles. Pode-se concluir que houve desgaste superficial de todos os grupos experimentais, independentemente da utilização de espátula plástica ou taça de borracha.
Enamel wear of teeth after microabrasion in vitro
Keywords: Microabrasion; Enamel; Wear; Permanent dentition; Microabrasão do esmalte; Desgaste do dente; Esmalte dentário; Dentição permanente